2022
DOI: 10.1111/jfpp.16573
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating the dry aging of bone‐in beef from Nellore cattle by the freeze/thaw process

Abstract: This study evaluated the effects of the freezing and thawing process on the quality characteristics and volatile organic compounds (VOC) of bone‐in ribeye roll from Nellore cattle during dry aging (up to 42 days at 4°C). Freezing increased evaporation (~3.2%) and boning (~2.5%) losses, which resulted in a 6.05% lower final average performance. Freezing also increased the psychrotrophic, and lactic acid bacteria count, without compromising the microbiological quality. On day 14, frozen samples had lower water a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…According to the literature, the MFI, which is a proxy allowing for the evaluation of post-mortem proteolysis, can explain more than 50% of the variation in beef tenderness and shows a high positive (r = 0.75) correlation with sensory tenderness and a negative (r = −0.72) correlation with WBSF values [ 20 ]. In the present study, although an inverse relationship was observed between these quality variables, neither myofibrillar proteolysis nor the WBSF was affected by the treatments, as described in earlier studies on Zebu cattle [ 21 , 41 ].…”
Section: Discussionsupporting
confidence: 71%
“…According to the literature, the MFI, which is a proxy allowing for the evaluation of post-mortem proteolysis, can explain more than 50% of the variation in beef tenderness and shows a high positive (r = 0.75) correlation with sensory tenderness and a negative (r = −0.72) correlation with WBSF values [ 20 ]. In the present study, although an inverse relationship was observed between these quality variables, neither myofibrillar proteolysis nor the WBSF was affected by the treatments, as described in earlier studies on Zebu cattle [ 21 , 41 ].…”
Section: Discussionsupporting
confidence: 71%
“…Tenderness is one of the most important factors in the perception of beef quality by consumers, and they are usually willing to pay more for tender meat. The industry has aged vacuum‐packed fresh beef at temperatures immediately above its freezing point (−1 to 1°C) for long enough (up to 3 weeks) to maximize their palatability before commercialization (Haddad et al, 2022). During aging, there is an increase in tenderness, in addition to the development of a characteristic flavor, due to the degradation of the myofibrillar structure by endogenous proteases (Lee, Sebranek, & Parrish, 1996).…”
Section: Introductionmentioning
confidence: 99%